Autoimmune Gastritis Accompanied by a Schwannoma Presenting as a Subepithelial Tumor - Yong Hwan Ahn; Kyo Bum Hwang; Geom Seog Seo (Yong Chan Lee, 2023)
Autoimmune gastritis (AIG), a chronic inflammatory disease occurs as a result of a complex interaction between host-related and environmental factors. AIG may progress to severe atrophic gastritis secondary autoimmune-mediated parietal cell destruction in the stomach. AIG can be diagnosed based on anti-parietal cell antibody tests and endoscopy, which reveals widespread gastric corpus atrophy in patients with low serum pepsinogen I levels, a low pepsinogen I/II ratio, and elevated serum gastrin levels on serological testing. Tissue biopsy findings, which include mucosal atrophy and lymphocytic infiltration of the lamina propria may be useful for diagnostic confirmation. Decreased gastric acid secretion causes hypergastrinemia and enterochromaffin-like (ECL) cell proliferation, which can lead to neuroendocrine tumor development. Additionally, an autoimmune response results in parietal and chief cell injury, and proliferating ECL cells are detected in the deep mucosal layers in patients with AIG. Therefore, this condition may easily be misdiagnosed as a subepithelial tumor, and establishing a differential diagnosis for other types of subepithelial tumor accompanied by AIG is challenging. We present the case of a 54-year-old woman who was diagnosed with AIG with a concomitant subepithelial tumor based on serologic tests and biopsy findings and underwent wedge resection, which confirmed diagnosis of a schwannoma.